Cysteine-sparing CADASIL mutations in NOTCH3 show proaggregatory properties in vitro - Wollenweber, Frank Arne; Bäzner, Hansjörg (Stroke, 2015)
Background and Purpose: Mutations in NOTCH3 cause cerebral autosomal-dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL), the most common monogenic cause of stroke and vascular dementia. Misfolding and aggregation of NOTCH3 proteins triggered by cysteine-affecting mutations are considered to be the key disease mechanisms. However, the significance of cysteine-sparing mutations is still debated. Methods: We studied a family with inherited small vessel disease by standardized medical history, clinical examination, MRI, ultrastructural analysis of skin biopsies, and Sanger sequencing of all NOTCH3 exons. In addition, we performed in vitro characterization of NOTCH3 variants using recombinant protein fragments and a single-particle aggregation assay. Results: We identified a novel cysteine-sparing NOTCH3 mutation (D80G) in 4 family members, which was absent in a healthy sibling. All mutation carriers exhibited a CADASIL typical brain imaging and clinical phenotype, whereas skin biopsy showed inconsistent results. In vitro aggregation behavior of the D80G mutant was similar compared with cysteine-affecting mutations. This was reproduced with cysteine-sparing mutations from previously reported families having a phenotype consistent with CADASIL. Conclusions: Our findings support the view that cysteine-sparing mutations, such as D80G, might cause CADASIL with a phenotype largely indistinguishable from cysteine mutations. The in vitro aggregation analysis of atypical NOTCH3 mutations offers novel insights into pathomechanisms and might represent a tool for estimating their clinical significance.